2017
DOI: 10.1177/0954408917742196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vibration signals to quantify displacement amplitude in the monitoring of vibration-assisted turning

Abstract: Vibration-assisted machining combines precision machining with small-amplitude tool vibration at high frequency to improve the fabrication process. It has been applied to a number of processes from turning to drilling to grinding. This work presents the validation of tool condition monitoring system based on vibration parameters. For this purpose, an experimental investigation is planned to acquire vibration signal data during the machining. This work primarily focuses on quantifying the presence of relative v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This trend agrees with previous works published [4]. As feed increases, vibrations vary and contribute to the surface finish [31]. With increased speed, SR, MRR, and Vib showed an increasing trend in the limits of (0.05 to 0.2 mm/rev) feed rate.…”
Section: Effect Of Feedsupporting
confidence: 92%
See 1 more Smart Citation
“…This trend agrees with previous works published [4]. As feed increases, vibrations vary and contribute to the surface finish [31]. With increased speed, SR, MRR, and Vib showed an increasing trend in the limits of (0.05 to 0.2 mm/rev) feed rate.…”
Section: Effect Of Feedsupporting
confidence: 92%
“…As per 'ISO-10816' standards for rotatingworkpiece, the amplitude of vibration up to 20 mm has a negligible impact on Tw. Tw effects when vibration amplitude in the workpiece ranges from 20 microns to 60 microns, and vibration amplitude beyond 60 microns needs attention [31]. From the results tabulated in Table 2, one can observe that as vibration amplitude is high, so is the surface roughness.…”
Section: Experimental Measures Of Outputs and Discussionmentioning
confidence: 99%
“…7a, the amplitude of cutter vibration increased when the spindle speed and feed per tooth are increased. Murthy et al [10] and Prasad [14] Fig. 7 a Interaction effect of process parameters on Y, b interaction effect of tool parameters on Y Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that surface roughness is greatly affected by feed rate and dimensional accuracy is affected by tool wear and tool vibrations. Prasad et al [14] investigated effect of relative vibration between the work piece and the tool on the surface roughness and tool wear in vibration-assisted turning of Ti-6Al-4 V. They used LDV for online data acquisition of tool vibration during the machining process. They concluded that the cutting speed has significant effect on tool vibration and tool wear, whereas the feed rate was found to be responsible for surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many scholars have studied the correlation between cutting vibration and tool wear and analyzed the impact of vibration on tool wear. Prasad et al (2016Prasad et al ( , 2019 analyzed the correlation between vibration amplitude and tool wear in dry turning of AISI 4140 steel using uncoated carbide insert DNMA 432.…”
Section: Introductionmentioning
confidence: 99%